I don't know who you are [videorecording (DVD)] - Clennon, Mark; Diaz, Anthony; Manuel, Nat Patricia (Darkstar Pictures, 2024)
Benjamin is a gay immigrant and working-class musician living in Toronto. One weekend, he is sexually assaulted by a stranger. As a fledgling freelance worker without health insurance, the drugs that Benjamin needs to avoid HIV infection after his assault are not easily accessible. He is pushed to his limit while trying to scrape together the funds for his treatment before time runs out. Director M.H. Murray creates a tense and powerful film, revolving around the disparity of the health care system, and one man's desperate attempt to find help and safety.